Analysis Of Students' Mathematical Representation Ability in View of Learning Styles - Rachmawati Khaerun Nisa; Reza Muhamad Zaenal (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Students' mathematical representation ability from the point of view of learning styles, we can see that learning styles play an important role in how students absorb mathematical information. The visual learning style involves using pictures, diagrams and other visual representations to understand math concepts. The auditory learning style involves a preference for listening to oral explanations or participating in discussions. Meanwhile, the kinesthetic learning style involves physical movement to gain an understanding of mathematics. This study aims to determine: 1) the representational ability of students who have a visual learning style, 2) the representational ability of students who have a kinesthetic learning style, 3) the representational ability of students who have an auditory learning style. In this study using descriptive qualitative research methods to determine the ability of mathematical representation which has a learning style for each student in class VII-F SMP Negeri 2 Kuningan. Data were collected through learning style questionnaires, representation ability tests and interviews with students. The results of the learning style questionnaire for the majority of students have a rich visual learning of 42%, kinesthetic 30% and auditory 28%. The results of the representation ability test showed that students with visual learning styles had high mathematical representation abilities, while the majority of students with auditory and kinesthetic learning styles were categorized as moderate. Interviews with students revealed that learning understanding can be understood by means of their learning styles. However, teachers face obstacles in choosing learning models that suit students' learning styles and need to understand individual learning needs. Students' activities in learning mathematics also still need to be improved, especially in the ability to discuss, conclude, and make summaries. Therefore, further efforts are needed to pay attention to differences in student abilities and develop appropriate strategies to increase student interaction and participation in learning mathematics.